Factors influencing the implementation of Malaysia Sustainable Palm Oil (MSPO) among organized oil palm smallholders in Malaysia / Abdul Halim A Hamid - A Hamid, Abdul Halim (2019)
Malaysia's oil palm industry plays a vital role in the growth of the agricultural sector by contributing to gross domestic product (GDP), foreign exchange and employment. The demand for oil palms continues to rise as it can produce high yields with low production costs. With conspicuous environmental destruction and climate change, consumers worldwide are all stirring towards sustainable production of commodities. As Indonesia (the main competitor of Malaysian oil palm) is moving towards Indonesia Sustainable Palm Oil (ISPO). This poses a significant threat to oil palm producers in Malaysia, including smallholders. Smallholders ' survival is vital and has played a major role in Malaysia's agricultural industry's progress. The objective of this study was to investigate the factors influencing the implementation of Malaysia's Sustainable Palm Oil (MSPO) among organized smallholders in Malaysia. The study was carried out to the organized smallholders in oil palm industry in Felda Chini Timur3, Pahang, Malaysia, Pahang was chosen as a convenience sample. Since the purpose of the study was to examine the factors influencing smallholder implementation of MSPO based on empirical evidence and primary information, a quantitative approach was adopted by the study. A questionnaire-based survey was used to extract information from the smallholders. The data gathered from the questionnaire survey was administered and analyzed quantitatively using IBM SPSS software. The result observed several socio-economic factors that could lead to implementation practices such as the age of smallholder, perceived benefits of MSPO, education level of smallholder, MSPO cost, knowledge of MSPO and MSPO government support. This study highlights the factors influencing Malaysia's implementation of Sustainable Palm Oil (MSPO) among Malaysian smallholders. It is important to identify the factors that influencing the level of MSPO implementation for future research and policy implementation. The most influencing factors identified toward the implementation of MSPO is the implementation cost of the MSPO practice and the government support of MSPO implementation. Thus, it is important for the government to play a more effective role as a catalyst to encourage smallholders to implement the sustainable practices